(untitled) (Global Journal of Human-Social Science, 2016)
This study investigated the effect of sectoral government expenditure on poverty level in Kenya Private Consumption per capita a measure of poverty was the independent variable while education health agriculture and infrastructure expenditures were the independent variables Time series data for the period of 1964-2010 was used and was tested for unit root using Augmented Dickey Fuller test whereby all variables were found to be integrated to I 1 A lag length of three was selected using Vector Autoregressive model Presence of co-integration was confirmed using the Johansen test which showed there was one co-integrating equation Vector Error Correction model indicated that there was a stable long run relationship between poverty level and sectoral government expenditure in Kenya The regression results indicated that agriculture and health expenditures have a positive and significant effect on poverty level while infrastructure expenditure has a negative and significant effect on poverty level The effect of education expenditure on poverty level was insignificant It is recommended that the government in Kenya increases expenditure allocation to agriculture and health sectors